Uji Efektivitas Luka Bakar Pada Kelinci (Oryctolagus cuniculus) Sediaan Salep Ekstrak Ikan Gabus (Channa striata) Dari Danau Tondano - Ahlan Sangkal; Rahmat Ismail; Adelin Liputo (Universitas Muhamadiyah Manado, 2020)
Cork Fish (Channa striata) is used for traditional medicine and is one of the economically important fish in Indonesia so that it contains protein and albumin which are important for health. The purpose of this study was to determine the level of effectiveness of the snakehead fish extract ointment on the healing of burns in rabbits (Oryctolagus cuniculus). Then burns in rabbits were observed for up to 11 days. The data analysis used was using the Independent Sample t-test with the help of Microsoft Excel. Based on the results of the research formula one can be the t value count 4,666 and the table t value 2,085 and the second formula obtained is the t value count of 2,185 and the table t value of 2,085 according totheresearch hypothesis is accept H1 then formula one dan formula two have an influence in the process of healing burns in rabbits (Oryctolagus cuniculus).